2005
DOI: 10.1177/003693300505000310
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Contained Rupture of Abdominal Aortic Aneurysm Presenting with Longstanding Back Pain

Abstract: Abdominal aortic aneurysm (AAA) is one of the important differential diagnoses of back pain which is often missed. Chronic contained rupture is a rare event that can cause diagnostic difficulties, presenting in different ways such as back pain, neuropathy or groin mass. We are presenting a case of 46-year-old man who presented with history of recurrent low back pain radiating to his left leg, associated with sensory deficit in the left thigh. His complaint proved to be resulting from chronic contained AAA leak. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…En ocasiones, la rotura de aneurisma aórtico abdominal puede contenerse, formando un hematoma a nivel retroperitoneal, evitando el desarrollo de shock hipovolémico agudo y, en muchas ocasiones, la muerte inminente del paciente. Descrito por primera vez por Szilagyi en 1965 (5), este cuadro se presenta en ocasiones como una lumbalgia o un dolor neuropático a nivel de raíces bajas, en función de su localización, de las estructuras colindantes y de la presión que ejerza este hematoma a nivel local (6,7).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En ocasiones, la rotura de aneurisma aórtico abdominal puede contenerse, formando un hematoma a nivel retroperitoneal, evitando el desarrollo de shock hipovolémico agudo y, en muchas ocasiones, la muerte inminente del paciente. Descrito por primera vez por Szilagyi en 1965 (5), este cuadro se presenta en ocasiones como una lumbalgia o un dolor neuropático a nivel de raíces bajas, en función de su localización, de las estructuras colindantes y de la presión que ejerza este hematoma a nivel local (6,7).…”
Section: Discussionunclassified
“…El comentado dolor lumbar o neuropático de raíces vertebrales bajas se puede justificar por varias consecuencias que produce la rotura del aneurisma, como son la erosión de las vértebras adyacentes debido a la pulsación arterial continua sobre las mismas (6,8), que puede llegar a producirse incluso sin la rotura del aneurisma (9), junto con la irritación de músculos y nervios a ese nivel, como el músculo psoas ilíaco o nervio femoral, por la hemorragia ocasionada, como aconteció en nuestro caso.…”
Section: Discussionunclassified
“…For instance, a retroperitoneal haematoma that places stress on a iliopsoas muscle can very well cause irritation of the femoral nerve, making it appear a femoral neuropathy. This may imply that a patient presenting with a sensory deficit of the anterior thigh could be someone who is in need of an immediate medical referral (Ramasamy et al, 2001;Al-Koteesh et al, 2005). Symptoms can result from compression (e.g.…”
Section: Chronic Contained Ruptured Aneurysmmentioning
confidence: 99%
“…Other differential diagnoses include any abdominal pathology related to the structures compressed. It is suggested that the atherosclerotic plaques from someone with an AAA can increase risk of ischemia and thus lead also to disc degeneration (Al-Koteesh et al, 2005). This means that anyone presenting with degenerative disc disease symptoms could also have an underlying AAA that was the initial cause.…”
Section: Chronic Contained Ruptured Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation